Potential role for the conservative management of warfare penetrating Shrapnel and bullets to the abdomen: an observational study - M Ezzedien Rabie; Mansour Al Asmari; Abdelelah Hummadi; Yahia Al Malki; Ahmad Abu Al Yazeed; Ahmad Al Hazmi; Yasser Almahdi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: the conservative management of selected cases of penetrating Shrapnel and bullet injuries to the abdomen, inflicted in the warzone, has not been previously reported. Material and methods: Patients, who sustained penetrating bullets or Shrapnel abdominal injuries in the battle field, were included in the study. Results: 39 consecutive patients were included in the study. They were all males with a mean age of 31 years. 4 (10.3%) patients had bullet injury, while 35 (89.7%) had Shrapnel injury. The injury was localized to the abdomen in only two cases (5%), while it involved the abdomen as well as other sites in the remaining 37 patients (95%). 13 patients (33.3%) underwent laparotomy in the first line hospital, while 26 (66.7%) were referred to our hospital without laparotomy. Out of these 13 laparotomies, 10 (77%) were positive therapeutic, while 3 (23%) were positive non therapeutic. In our hospital, 10 (77%) out of these 13 patients needed only continued post operative care while 3(23%) needed relaparotomy. In the 26 patients who were referred to our hospital without laparotomy, 4 (15.4%) needed laparotomy, while conservative management was followed in 22(84.6%) with only one failure. All laparotomies performed in our hospital were positive therapeutic ones. At the end of the study, patients were contacted by phone. 23 patients, were found in good health, two patients had minor complaints, while. 14 could not be contacted. Conclusion: a subset of patients with penetrating Shrapnel and bullet injury to the abdomen, who show no frank indication for laparotomy, could be treated conservatively. The clinical evaluation should be augmented with contrast enhanced abdominal CT scan. Preparedness to operate if conditions change, should be an indispensable part of the treatment plan. By adopting this policy, a reduction in the rates of positive non therapeutic or negative laparotomy, could be anticipated.